Aryltetralone lignans and 7,8-seco-lignans from Holostylis reniformis - Da Silva, Tito [UNESP]; Lopes, Lucia M.X. [UNESP] (Elsevier, 2004)
Aryltetralone lignans and two 7,8-seco-lignans were isolated from the acetone and hexane extracts of the roots of Holostylis reniformis, together with (-)-galbacin. Their structures were determined by spectroscopic methods. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Aristolochiaceae; Aryltetralone lignans; Holostylis reniformis; Lignans; Neolignans; Seco-lignans; 4' o methylenshicine; 7,8 seco holostylone a; 7,8 seco holostylone b; 8' epiaristoligone; 8,8' epiaristoligone; 8,8' epiholostylone; acetone; aristoligone; aristotetralone; galbacin; hexane; Holostylis reniformis extract; holostylone; ketone derivative; lignan; plant extract; unclassified drug; controlled study; drug isolation; drug structure; nonhuman; plant root; structure analysis; Circular Dichroism; Molecular Structure; Nuclear Magnetic Resonance, Biomolecular; Plant Extracts; Plant Roots; Tetralones